2012
DOI: 10.1136/bmjopen-2011-000692
|View full text |Cite|
|
Sign up to set email alerts
|

Detecting and measuring deprivation in primary care: development, reliability and validity of a self-reported questionnaire: the DiPCare-Q

Abstract: ObjectivesAdvances in biopsychosocial science have underlined the importance of taking social history and life course perspective into consideration in primary care. For both clinical and research purposes, this study aims to develop and validate a standardised instrument measuring both material and social deprivation at an individual level.MethodsWe identified relevant potential questions regarding deprivation using a systematic review, structured interviews, focus group interviews and a think-aloud approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 38 publications
0
47
0
2
Order By: Relevance
“…Sosyal eşitsizliklerle tanımlanan sosyal yoksunluğun özellikle dışlanma, izolasyon ve endişe gibi yarattığı sonuçların sağlık üzerindeki etkileri birçok çalışma ile ortaya konulmuştur. 13,18,19 Bu bakış açısıyla sosyal yoksunluk, yoksulluğun önemli bir boyutudur ve maddi yoksunluktan ayrılması gerekmektedir. DiPCare-Q'nun geleneksel yoksulluk ve maddi yoksunluk ölçümleri Birinci basamak sağlık hizmetlerinde yoksul bireylerin belirlenmesi, sağlıkta eşitsizliklerinin giderilmesine yönelik çalışmalar geliştirmenin ilk adımıdır.…”
Section: Discussionunclassified
“…Sosyal eşitsizliklerle tanımlanan sosyal yoksunluğun özellikle dışlanma, izolasyon ve endişe gibi yarattığı sonuçların sağlık üzerindeki etkileri birçok çalışma ile ortaya konulmuştur. 13,18,19 Bu bakış açısıyla sosyal yoksunluk, yoksulluğun önemli bir boyutudur ve maddi yoksunluktan ayrılması gerekmektedir. DiPCare-Q'nun geleneksel yoksulluk ve maddi yoksunluk ölçümleri Birinci basamak sağlık hizmetlerinde yoksul bireylerin belirlenmesi, sağlıkta eşitsizliklerinin giderilmesine yönelik çalışmalar geliştirmenin ilk adımıdır.…”
Section: Discussionunclassified
“…Among these studies, Lee et al [18] reported a cumulative socioeconomic risk for cognitive impairment in elderly. In line with this cumulative approach, we meant to focus on the association between multiple vulnerabilities (the concept of ‘psychosocioeconomic precariousness') and cognitive ageing, using psychosocial variables in addition to occupation, education and income, as it has been recently proposed [19,20]. Therefore, the novelty of this research is that we combined a cumulative approach of precariousness (each item is scored 1 point and considered as providing additional precariousness) with a multidimensionality definition of precariousness including indicators of poor socioeconomic status and psychosocial vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [18] measured socioeconomic status with four indicators, i.e., education, income, wealth and occupation in 4,155 subjects aged ≥65 years, and showed that the combined effect of such factors on cognitive decline was stronger than the effect of each factor considered separately. Moreover, the use of psychosocial variables in addition to occupation, education and income has been recently proposed [19,20]. Indeed, numerous authors have underlined the multidimensional nature of precariousness, and the necessity to consider not only markers of individual's economic resources but also markers of social support, such as ‘living with a partner' or ‘whether an individual goes on holiday' [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' occupation, educational level, or income are often used as proxies for socioeconomic status [2]. More rarely a dedicated questionnaire is used to obtain a deprivation score [3], [4]. Social inequalities in health are found worldwide and have consequences for morbidity and mortality [5].…”
Section: Introductionmentioning
confidence: 99%